Creating Shared Value: Relationality Perspective - Lindrawati Lindrawati; Armada Riyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Creating shared value shows that the company is able to align the company's competitive policy, profit-oriented businesses, while improving the social and economic welfare of the communities where the company operates by incorporating social issues into the company's strategy. This is a form of connection between the company and the society where the company's daily operations are related to the society so that the company has society welfare. This literature study discusses about the creation of shared value from a relationality perspective. A harmonious relationship between the company and the society will bring advantages and benefits to the company and society, where the company will gain a competitive advantage while increasing the welfare of the society and this can improve the company's image in the eyes of the society so that it can improve the company’s sustainability in the future. Keywords: Creating Shared Value, Relationality